Giant Condyloma Accuminata in Pregnancy, Use of Trichloroacetic Acid combined with electrocauterization and excision Procedure: A Case Report - Putri Cinthya Ismihari; Riyana Noor Oktaviyanti (Universitas Muhammadiyah Purwokerto, 2021)
Condyloma acuminata is a sexually transmitted disease caused by the Human Papilloma Virus (HPV). During pregnancy, condyloma acuminata can proliferate rapidly due to changes in immunity and increased blood supply. One of the safest therapeutic modalities is trichloroacetic acid (TCA). Electrocautery is another modality in pregnant patients. A 16-year-old woman, 6-months pregnant, complained of a wart-like lump in the pubic area getting more prominent since the last two weeks and covering the vagina surface. The lump is not itchy and painless. From history-taking it was found that patient often changes partners. On physical examination, the lesions were multiple papules with a verrucous surface. The results of the work-up showed a positive acetowhite test. Patients are then treated with a TCA of 80-90% during pregnancy and followed by electrocautery and excision during cesarean section. The results of 80-90% TCA treatment followed by electrocautery and excision were satisfactory, and there were no recurrences when the patient went for a follow-up. TCA is a substance that is caustic and can erode skin and mucous membranes. TCA works by coagulation of proteins which causes dryness of cells and tissues. TCA is safe for pregnant women. Combination of TCA 80-90% with electrocautery and excision, in this case, proved to be effective with no sign of recurrence. The combination of TCA therapy with electrocautery and excision has proven effective and safe for pregnant patients.